2019
DOI: 10.1097/cm9.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological predictors of aphasia recovery in patients with large left-hemispheric infarction

Abstract: Background:Although the rehabilitation of aphasia has been extensively studied, the prediction of language outcome still has not received sufficient attention. The aim of this study was to predict the language outcome using mismatch negativity (MMN) in patients with large left-hemispheric infarction.Methods:MMN was elicited by an oddball paradigm in which a standard tone (1000 Hz) and deviant tone (1500 Hz) were presented at 90% and 10% of the number of tones, respectively. The mean amplitudes and laterality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In PSA patients, monitoring power in the theta, alpha, and beta frequency bands via EEG can serve as both a repeated and a sensitive measure to assess function and detect changes in patients with chronic aphasia ( 62 ). Both N400 and MMN are components closely related to language processing, and the abnormalities in two components suggest difficulties in processing and understanding semantic information as well as reduced sensitivity and adaptability to rule violations in language ( 50 , 63 ). Reduction of the N400 is associated with language improvement ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PSA patients, monitoring power in the theta, alpha, and beta frequency bands via EEG can serve as both a repeated and a sensitive measure to assess function and detect changes in patients with chronic aphasia ( 62 ). Both N400 and MMN are components closely related to language processing, and the abnormalities in two components suggest difficulties in processing and understanding semantic information as well as reduced sensitivity and adaptability to rule violations in language ( 50 , 63 ). Reduction of the N400 is associated with language improvement ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the N400 is associated with language improvement ( 31 ). In another longitudinal study utilizing the MMN paradigm, it’s found that the laterality index of MMN amplitudes at approximately 2 weeks post left-hemisphere stroke serve as more sensitive predictors of language outcome, among which the laterality index over the perisylvian area exhibits the best predictive value ( 50 ). However, there is a limited amount of research investigating the changes in MMN and N400 in response to TMS before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation